Studi Komparasi Konsep Pendidikan Perspektif Jean Jackquess Rosseau dan Abdullah Nashih Ulwan - Cindy Wulandhari; Muh. Wasith Achadi (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The reality found in Indonesia, education has not been able to carry out its role well. The various concepts adopted make education dynamic, but have not shown significant output. Curriculum changes based on climate change government, science, and technology in Indonesia sometimes make education less targeted. In relation to Islamic Education, there is a kind of reluctance to adopt Western thought to answer the problem, while according to historical surveys, scientific civilization after the success of Islam collapsed, much absorbed by the West. This research intends to compared the concept of education according to Western and Islamic figures to find solutions, especially in the scope of Islamic Education. This research uses a qualitative type of descriptive-analytical approach using library research. The results showed that the thoughts of the two figures have common ground and similarities in the concept section of the educational stage, goals, teacher, student, materials, and methods. But in the stages, objectives, teacher, student, methods, and materials, there are differences. Abdullah Nashih Ulwan and Jean Jackquess Rosseau had a good concern and concept towards education. Keywords : Education, Jean Jackquess Rosseau, Abdullah Nashih Ulwan.